Superficial micro-strength of artificial mills of acrylic resin used in rehabilitating dentistry, three trade marks. In-vitro studio - Cruz Gallegos, Paul (2018)
Objectives: The purpose of the present study was to determine and compare the surface microhardness of three brands of artificial molars to verify if there is a significant difference between them. Materials and Methods: artificial molars were used based on acrylic resin, 15 lower molars of each brand TRILUX®, Gnathostar® and Duratone-n®, the samples were prepared making a coronal cross section to obtain a flat, smooth surface and polished, it was placed in pvc dies with 1.5cm Autopolymerizable acrylic, the surface to be analyzed was dyed blue, to then be taken to the Duroline-M Metkon Microdurometer where 3 indentations were made for each sample with a force of 200 grams during 15 seconds obtaining the results in units of Vickers (Hv). Results: The TRILUX® brand molars had higher surface microhardness with an average of 24,306 ± 1.41Hv, followed by the morals Duratone-n® with 22.21 ± 0.72 Hv and finally Gnathostar® with 19.82 ± 0.66 Hv, by statistical tests. He was able to confirm tha